Analysis of the attitudes and perceptions of prospective science teacher students towards stem learning - Oktavianty, Erwina; Syaiful B. Arsyid (Jurnal Pendidikan Informatika dan Sains, 2024)
This research aims to analyze the attitudes and perceptions of prospective science teacher students in STEM (Science, Technology, Engineering and Mathematics) learning. This research uses a survey method and is analyzed descriptively to get a true picture. The sample in this study was 62 students consisting of physics education, chemistry education and science education study programs from 4 universities in the West Kalimantan region. Data analysis was carried out qualitatively based on the results of distributing a questionnaire on attitudes and perceptions of prospective science teacher students. Based on the results of data analysis obtained, prospective science teacher students have good attitudes and perceptions towards STEM learning. As for every aspect of students' attitudes and perceptions towards the STEM learning carried out, students have attitudes and perceptions in the category of sufficient understanding that prospective teacher students recognize an interest in STEM learning, have sufficient competence and performance in learning in the STEM field and have an interest and sense of ownership. it is good. The average attitude and perception of students shows 2.81, which means it is quite good.